Application of Edible Coating Based on Oil Palm Derivatives with the Addition of Chitosan to the Quality of Salak Pondoh Fruit (Salacca edulis Reinw var.) Wonosobo during Storage: Aplikasi Edible Coating Berbasis Turunan Kelapa Sawit dengan Penambahan Kitosan Terhadap Mutu Buah Salak Pondoh (Salacca edulis Reinw var.) Wonosobo selama Penyimpanan - Permana, Galih; Widyasanti, Asri; Handayani, Wiwik (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2025)
This study evaluated the effectiveness of edible coating based on oil palm derivatives with the addition of chitosan in maintaining the quality of Pondoh Wonosobo salak fruit during storage. The edible coating is formulated from palm stearin esters (the result of a synthesis reaction) as well as chitosan, carrageenan, GMS, and Tween 80 additives. This study used a completely randomized design (CRD) with two treatments, namely control and coating, and data analysis using descriptive statistics in the form of averages and standard deviations presented in the form of quality change graphs. Salak was coated with a selective coating and/ , stored at room temperature for 12 days, with the observed parameters including weight loss, hardness, total dissolved solids, acidity, vitamin C, and moisture content. The results showed that edible coating was effective in suppressing quality degradation, characterized by lower weight loss (24.1% vs. 48.7% control). The coating treatment also showed a tendency to maintain hardness, total dissolved solids, vitamin C, and moisture content better than controls. This innovation has the potential to extend the shelf life of salak.